Increasing Knowledge About Sexually Transmitted Infections Using The Small Group Discussion (SGD) Approach Among Students At SMP N 1 Bulango Selatan - Zainuddin, Zainuddin; Yusuf, Nur Ayun R.; Luadu, Nurmarila; Pilo, Wisnawati; Suardi, Suardi; Basri.K, Sarinah (Borneo Community Health Service Journal, 2024)
Sexually Transmitted Infections (STIs) are infections caused by microorganisms that are transmitted through sexual contact. The World Health Organization (WHO) announced that more than one million people are infected with STIs every day. Adolescence is a transitional developmental period between childhood and adulthood which experiences many changes and requires guidance and information, especially regarding health. One appropriate strategy to increase youth knowledge is through counseling using the SGD or small group discussion approach. This outreach aims to increase the knowledge of teenagers at SMP N 1 Bulango Selatan about sexually transmitted infections. This outreach activity used a small group discussion outreach strategy which was attended by 20 students of SMPN 1 South Bulango. To measure participants' knowledge, a pre-test and post-test were used with the method used, namely PDCA (Plan-Do-Check-Act). The results of the counseling carried out showed an increase in students' knowledge at SMPN 1 Bulango Selatan about STIs with the average score after the counseling increasing by 33 points. This shows that SGD is effective in increasing knowledge in extension. From this counseling, it can be concluded that students' knowledge at SMPN 1 Bulango Selatan has increased. So it is hoped that students can prevent STIs and disseminate information to the public.